Effectiveness of group cognitive behavioral-based therapy on pain, functional disability and psychological outcomes among knee osteoarthritis patients in Malaysian government hospitals - Foo, Chai Nien (2017)
Background: Knee osteoarthritis (OA) mainly causes pain, stiffness and muscle weakness. It also affects individual’s physical functioning. It has great impact on individual’s quality of life and wellbeing. Anti -inflammatory drugs and knee replacement are the mainstay methods in the management of knee OA in Malaysia. It is still noted that individuals with knee OA suffer from low quality of life. Non-pharmacological interventions are still a driving force in managing knee OA pain. Cognitive behavioral-based therapy is a first line psychosocial treatment which is more applied in chronic pain conditions. Evidence of effectiveness of cognitive behavioral-based therapy in treating OA knee pain is lacking. Objective: This study aimed to develop, implement, and evaluate the effectiveness of a cognitive behavioral-based therapy module in treating knee pain, functional disability and psychological outcomes for patients with knee OA. Methodology: A two arm parallel-group unblinded randomized controlled study design was used in this study. Three hundred patients aged 35 to 75 years diagnosed with knee OA (Kellgren grade ≥2 and visual analogue scale (VAS) score 40 or more) were recruited from Orthopaedics clinic of Hospital Putrajaya and Hospital Serdang, Malaysia. A cognitive behavioral-based therapy module was developed based on the cognitive-behavioral model. Eligible patients were randomized by applying independently operated computer- generated random sequence system with the block randomization of six (http://random-allocation-software.software.informer.com/2.0/).Participants in intervention group (n=150) received a three sessions of a group cognitive behavioral intervention (two and a half hour for each session) in addition to standard routine care and participants in control group (n=150) received standard routine care. A set of self-administered validated and reliable structured questionnaire was used for data collection. Data was collected at baseline, immediate, one month and six months post treatment. Primary outcome measure was knee pain intensity. Secondary outcome measures included functional disability (daily living and sport), depression, anxiety, stress, fear-avoidance beliefs (physical activity and work), pain catastrophising and pain self-efficacy. Data collected was analyzed using SPSS software with the application of mixed design repeated measured analysis of variance. Results: One hundred and nineteen (79%) participants in the intervention group and 111 (74%) participants in the control group were included in the analysis at six months. The Knee injury and Osteoarthritis Outcome Score (KOOS) knee pain scores improved substantially in the intervention group, but not in the control group. The mean change in the KOOS knee pain score was 8.9 points (95% CI -11.23 to -6.62, p=0.0001) higher (less knee pain intensity) in the intervention group. Functional disability in daily living, depression, anxiety, pain catastrophising, and pain self-efficacy level improved significantly in the intervention group (p<0.05). Functional disability in sport, stress, and fear-avoidance beliefs in physical activity and work did not differ significantly between groups (p>0.05). Conclusion: The cognitive behavioral-based therapy module is effective in reducing knee pain intensity, functional disability in daily living, depression, anxiety, pain catastrophising, and improving pain self-efficacy level in this knee OA population.